[PP.18.01] DECREASED CIRCULATING T REGULATORY LYMPHOCYTES IN OBESE PATIENTS UNDERGOING BARIATRIC SURGERY. (September 2017) - Rosei, C. Agabiti; Rossini, C.; Mittempergher, F.; Titi, A.; Portolani, N.; De Ciuceis, C.; Caletti, S.; Coschignano, M.A.; Trapletti, V.; Porteri, E.; Pileri, P.; Rosei, E. Agabiti; et al.
Abstract : Objective: It has been previously demonstrated that T lymphocytes may be involved in the development of hypertension and microvascular remodeling, and that circulating T effector lymphocytes may be increased in hypertension (De Ciuceis C et al, Am J Hypertens 2016 Sep 21 online printing; Itani HA et al. Hypertension 2016; 68:123–132). In particular, Th1 and Th 17 lymphocytes may contribute to the progression of hypertension and microvascular damage while TREG lymphocytes seem to be protective. However, no data is avaliable about patients with severe obesity, in which pronounced microvascular alterations were observed (De Ciuceis C et al, Hypertension 2011; 58:29–36). Design and method: We have investigated 32 severely obese patients undergoing bariatric surgery, as well as 24 normotensive lean subjects and 11 hypertensive lean subjects undergoing an election surgical intervention. No sign of local or systemic inflammation was present in any subject or patient. A peripheral blood sample was obtained before surgery for assessment of CD4+ T lymphocyte subpopulations. Lymphocyte phenotype was evaluated by flow cytometry in order to assess T-effector and T-regulatory (TREG) lymphocytes. Subsets of TREGS were defined as follows: -TREGS recent thymic emigrants (RTE), directly derived from thymus: CD31+; -TREGS naïve: CCR7+CD45RA+; -TREGS central memory (CM): CCR7+CD45RA-; -TREGS effector memory (EM): CCR7-CD45RA-; -TREGS terminal differentiated effector memory (TDEM): CCR7-CD45RA+. Results: Results are summarized in the Table (*p < 0.05, **p < 0.01, ***p < 0.001 vs. lean normotensives; #p < 0.05, ##p < 0.01, ###p < 0.001 vs. lean hypertensives). A marked reduction of several TREG subpopolations was observed in obese patients compared with controls, together with an increased in some T-effector cells. Figure. No caption available. Conclusions: TREG lymphocytes are clearly reduced in severely obese patients, possibly contributing to the development of marked microvascular alterations previously observed in such a population.